Answer:
-2
Assumption:
Find the value of x such that
.
Step-by-step explanation:
![(f+g)(x)=0](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3D0)
![f(x)+g(x)=0](https://tex.z-dn.net/?f=f%28x%29%2Bg%28x%29%3D0)
![(x^2-2x)+(6x+4)=0](https://tex.z-dn.net/?f=%28x%5E2-2x%29%2B%286x%2B4%29%3D0)
Combine like terms:
![x^2+4x+4=0](https://tex.z-dn.net/?f=x%5E2%2B4x%2B4%3D0)
This is not too bad too factor on the left hand side since 2(2)=4 and 2+2=4.
![(x+2)(x+2)=0](https://tex.z-dn.net/?f=%28x%2B2%29%28x%2B2%29%3D0)
![(x+2)^2=0](https://tex.z-dn.net/?f=%28x%2B2%29%5E2%3D0)
So we need to solve:
![x+2=0](https://tex.z-dn.net/?f=x%2B2%3D0)
Subtract 2 on both sides:
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
Let's check:
![(f+g)(-2)](https://tex.z-dn.net/?f=%28f%2Bg%29%28-2%29)
![f(-2)+g(-2)](https://tex.z-dn.net/?f=f%28-2%29%2Bg%28-2%29)
![((-2)^2-2(-2))+(6(-2)+4)](https://tex.z-dn.net/?f=%28%28-2%29%5E2-2%28-2%29%29%2B%286%28-2%29%2B4%29)
![(4+4)+(-12+4)](https://tex.z-dn.net/?f=%284%2B4%29%2B%28-12%2B4%29)
![(8)+(-8)](https://tex.z-dn.net/?f=%288%29%2B%28-8%29)
![0](https://tex.z-dn.net/?f=0)
0 was the desired output of
.
5 2/3 = 17/3 = 34/6
8 5/6 = 53/6
34/6 - 53/6 = -19/6 = -3 1/6
Answer:
Yes, x + 12
Step-by-step explanation:
Simplify the following:
3 x - 2 x + 12
Grouping like terms, 3 x - 2 x + 12 = (3 x - 2 x) + 12:
(3 x - 2 x) + 12
3 x - 2 x = x:
Answer: x + 12
Answer:
-28
Step-by-step explanation:
6+(-34)
6-34= -28 that is the simplified form though the question isnt clear